There is no free benchmark: An institutional view of legal AI benchmarking - Neel Guha; Andy K. Zhang; Christine Tsang; Christopher D. Manning; Julian Nyarko; Daniel E. Ho (Proceedings of the National Academy of Sciences, 2026)
Despite substantial excitement around the use of AI in law, little information exists on the performance and associated risks of the domain’s widely marketed tools. Recent work, for instance, has demonstrated the significant potential for “hallucinations”—wherein models make up facts, law, and precedent—leading Chief Justice Roberts to spotlight this risk in his annual report on the judiciary. We argue that there is a need for public AI benchmarking in law. First, relative to other AI application domains, the legal AI ecosystem lacks legibility—there is little information about the design and performance of many commercial legal AI systems. Legal AI has not benefited from the types of benchmarking that have catalyzed, measured, and informed AI innovation and responsible use in other domains. Second, we articulate the challenges of the institutional design of benchmarking. We illustrate how benchmarks can be captured, watered down, and abused. Careful institutional design around the why, who, what, and how of benchmarking will be critical to navigate difficult tradeoffs of transparency, objectivity, expertise, and resources. Third, addressing legal AI’s illegibility requires matching institutional models to available resources and constraints. Rather than advocating for a single “best” approach to benchmarking, we show how benchmarking strategies depend on available resources.